P14.63 The use of TTFields for newly diagnosed GBM patients in Germany in routine clinical care (TIGER: TTFields in Germany in routine clinical care) - Bähr, O (Neuro Oncol, 2019)
BACKGROUND: Despite various clinical phase 3 trials, survival for the most common brain tumour, glioblastoma (GBM), has not improved since 2005. Alternating electric fields with low-intensity and intermediate frequency, known as tumor treating fields (TTFields) were shown to inhibit cancer cell division. In the EF-14 phase 3 trial, the addition of TTFields to adjuvant temozolomide (TMZ) chemotherapy demonstrated significant extension of median overall, progression-free and long-term survival in newly diagnosed GBM (ndGBM) patients. As there is very high interest among prescribing physicians from all disciplines in Germany to further evaluate these effects in routine clinical care, the aim of the TIGER study is to assess safety and efficacy of TTFields in routine clinical care as well as reasons for patients refusing TTFields treatment, changes in quality of life within 4 months after start of therapy, treatment duration and compliance. METHODS: The TIGER study is a multi-centre, prospective, non-interventional study in Germany (NCT03258021). All ndGBM patients who are eligible for TTFields therapy are asked for consent for study participation and comprehensively introduced to the therapy to allow them to make a conscious positive or negative therapy decision. At baseline and 2–4 months after treatment start, demographic data as well as the QoL and reasons for therapy decision are evaluated applying the EORTC-QLQ-C30/BN-20 and TTFields questionnaire, respectively. A number of about 1000 patient is planned (500 in each arm with positive and negative treatment decision, respectively) with a follow-up period of 18 months. RESULTS: At the time point of the last data cut-off (March 2019), more than 460 patients in the trial have made a decision for or against treatment with TTFields. Within this population, more than 80% of patients agreed to undergo TTFields therapy. The median age of patients included in the trial is actually 58.4 years (range 19–85). In this population 47 % received complete resection, 32 % partial resection and 22 % biopsy. CONCLUSION: Systematic and prospective data analysis for the use of TTFields in routine clinical care including patient’s therapy decision can be assessed in the TIGER trial. Additionally, the study supports the evaluation of treatment duration and usage rate, which could drive future analysis of TTFields treatment duration. Most recent data will be presented at the EANO annual meeting.